2002
DOI: 10.1021/ma012250l
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Anionic Polymerization of Methyl Bicyclobutane-1-carboxylate

Abstract: Introduction. Bicyclobutanes carrying electronwithdrawing substituents at the 1-and/or 3-positions are a remarkable class of reactive monomers. Either free radical or anionic polymerization occurs readily across the B-like 1,3-bond to give high molecular weight polymers consisting of 1,3-linked cyclobutane rings. 1 Such polymers have interesting properties including high glass transition temperatures, chemical and thermal stability, superior optical clarity, and resistance to depolymerization.1,3-Disubstituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Thus our trial to obtain high 28 The benzylamino group in the PMMA could be removed by the treatment with H 2 /Pd-C in THF to afford a PMMA with a primary amino functionality at the chain end ( Figure 3); the characteristic signals due to benzylamino group in its ammonium salt form [Ph; 7.4, 7.6 ppm, CH 2 ; 4.2 ppm, (Figure 3b)] completely disappered in the spectrum of the product (Figure 3a). Thus, BnTMSNLi can be regarded as a lithium amide doubly protected with TMS and benzyl groups, and equivalent to TMS 2 NLi; with the latter lithium amide, the control of MMA polymerization was much difficult (see Table I, ref 26), probably due to the low nucleophilicity. 25 Other Polymerization Systems Anionic polymerization of MMA in THF is a versatile method for synthesis of PMMA with controlled molecular weight.…”
Section: Identification Of N-benzylmethacrylamidementioning
confidence: 99%
See 1 more Smart Citation
“…Thus our trial to obtain high 28 The benzylamino group in the PMMA could be removed by the treatment with H 2 /Pd-C in THF to afford a PMMA with a primary amino functionality at the chain end ( Figure 3); the characteristic signals due to benzylamino group in its ammonium salt form [Ph; 7.4, 7.6 ppm, CH 2 ; 4.2 ppm, (Figure 3b)] completely disappered in the spectrum of the product (Figure 3a). Thus, BnTMSNLi can be regarded as a lithium amide doubly protected with TMS and benzyl groups, and equivalent to TMS 2 NLi; with the latter lithium amide, the control of MMA polymerization was much difficult (see Table I, ref 26), probably due to the low nucleophilicity. 25 Other Polymerization Systems Anionic polymerization of MMA in THF is a versatile method for synthesis of PMMA with controlled molecular weight.…”
Section: Identification Of N-benzylmethacrylamidementioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] More recently, the authors have reported that t-BuLi/bis(2,6-di-tert-butylphenoxy)ethylaluminum [EtAl(ODBP) 2 ] initiating system was effective for stereospecific living polymerization of methacrylates, 20 acrylates 25 and methyl bicyclobutane-1-carboxylate. 26 These exam-ples illustrate utility of organoaluminum compounds (Lewis acid) in the stereocontrol of anionic polymerization with organolithium initiators.…”
mentioning
confidence: 96%
“…Other stereoregular polymers were also obtained in the Lewis acid‐assisted anionic polymerization of methyl bicyclobutane‐1‐carboxylate. Although methylaluminum bis‐hindered phenoxide gave approximately 75% trans enchainment, the ethylaluminum analogue gave 92% trans 12. Further study of this monomer and methyl 1‐cyclobutenecarboxylate will be reported soon.…”
Section: Polymer Stereochemistrymentioning
confidence: 88%
“…Classical anionic polymerizations of the bicyclobutane 1‐nitrile and 1‐ester monomers occurred but gave modest yields of low polymers. Recently, our collaborators in Kitayama's group at Osaka demonstrated Lewis acid‐assisted anionic polymerization of the 1‐ester to obtain highly stereoregular polymers 12. The analogy between bicyclobutane and vinyl copolymerization even extended to the use of Lewis acids to enhance the electrophilicity of the electron‐poor bicyclobutane.…”
Section: Bicyclobutanesmentioning
confidence: 99%
“…In the previous paper, 4 we reported the anionic polymerization of MBCB with tert-butyllithium (t-BuLi)/bis(2,6-di-tertbutylphenoxy)ethylaluminum [EtAl(ODBP) 2 ] in toluene at À78 C gave transtactic polymers (trans contents > 90%) in high yields. This kind of favorable effect of aluminum bisphenoxides on the anionic polymerization has been well demonstrated in stereospecific living polymerizations of methacrylates and acrylates.…”
mentioning
confidence: 99%